2019
DOI: 10.2196/14110
|View full text |Cite
|
Sign up to set email alerts
|

Areas of Interest and Stigmatic Attitudes of the General Public in Five Relevant Medical Conditions: Thematic and Quantitative Analysis Using Twitter

Abstract: Background Twitter is an indicator of real-world performance, thus, is an appropriate arena to assess the social consideration and attitudes toward psychosis. Objective The aim of this study was to perform a mixed-methods study of the content and key metrics of tweets referring to psychosis in comparison with tweets referring to control diseases (breast cancer, diabetes, Alzheimer, and human immunodeficiency virus). Methods Each tweet’s conte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 63 publications
4
36
1
1
Order By: Relevance
“…This finding is in agreement with other research 27 that 41% to 66% of posts on diseases and conditions are nonmedical. 27 We identified that 353 posts with a statin mention contain an adverse event report (3.0% of 11 852), which is similar to rates in the literature ranging from 0.2% to 8.0% of posts. 25 Our research demonstrates that although many posts on Twitter are of a trivial nature, 52…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This finding is in agreement with other research 27 that 41% to 66% of posts on diseases and conditions are nonmedical. 27 We identified that 353 posts with a statin mention contain an adverse event report (3.0% of 11 852), which is similar to rates in the literature ranging from 0.2% to 8.0% of posts. 25 Our research demonstrates that although many posts on Twitter are of a trivial nature, 52…”
Section: Discussionsupporting
confidence: 68%
“…Twitter is a convenient platform to use because of the public availability of posts and the relative ease of collecting massive amounts of data. 27 Twitter is the third most popular social media platform in the United Kingdom 28 and is used by one-quarter of people in the United States. 29 All data used in this study were collected according to the Twitter terms of use and were publicly available at the time of collection and analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A wide variety of health topics have been analyzed so far, including infectious diseases, mental disorders, and chronic diseases [ 11 ]. For example, previous studies have quantitatively analyzed Twitter data to assess people’s attitudes toward mental illness [ 13 , 14 ]. In addition to YouTube, various sources were used to retrieve health-related data, including search engines, blogs, forums, and social media platforms such as Google, Bing, Baidu, Yahoo, Twitter, and Facebook [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that awareness initiatives trigger conversations and social responses to eating disorders that would not have occurred otherwise. The total number of tweets related to the 3 groups of hashtags we analyzed over a period of 12 days was higher than the numbers of tweets associated with other mental health conditions [ 22 ]. However, the interest in eating disorders shown by the American media overall can be classified as low [ 23 ].…”
Section: Discussionmentioning
confidence: 99%